A new species of Corinnella Thomas & Dominique, 2006 (Ephemeroptera: Baetidae) - Boldrini, R.; Salles, F. F.; Pes, A. M.o. (Zootaxa, 2013)
The monotypic genus Corinnella Thomas & Dominique, 2006, was described based on nymphs from French Guyana, and since the original description nothing has been added to knowledge of its systematics. The aim of the present paper is to describe a new species of the genus from Northern Brazil, to improve its diagnoses, and to report the genus for the first time from Brazil. The new species can be recognized by: labrum with discernible anteromedial emargination and process; posterior margin of terga IV with rounded spines; and tarsal claw with seven to nine denticles, with the outer and inner denticles distinctly longer than the others.